Effect of Heat Treatment on the Formation and Distribution of Dispersoid Particles in AlMgSi (Global Journal of Science Frontier Research, 1969)
In this paper we studied the effect of heat treatment on the formation and distribution of dispersoid particles which were formed as a function of heat treatment in AlMgSi alloy containing transition elements in AlMgSi alloy which contained the transition elements such as Mn and Cr. The extrapolation technique of Cliff et al (1983) has been used to determine the composition of dispersoid particles.
Keywords: AlMgSi alloys; dispersoids; precipitation; recrystallization